Properties of Kumaraswamy binary Distribution and compare methods of estimating parameters - عبد احمد رزاق; شمال اياد حبيب (Journal of Economics and Administrative Sciences, 2020)
The recent development in statistics has made statistical distributions the focus of researchers in the process of compensating for some distribution parameters with fixed values and obtaining a new distribution, in this study, the distribution of Kumaraswamy was studied from the constant distributions of the two parameters. The characteristics of the distribution were discussed through the presentation of the probability density function (p.d.f), the cumulative distribution function (c.d.f.), the ratio of r, the reliability function and the hazard function. The parameters of the Kumaraswamy distribution were estimated using MLE, ME, LSEE by using the simulation method for different sampling sizes and using preliminary values of the parameters. The parameter rating was compared based on the average error squares of the parameters. The results indicated that estimating the parameters as far as possible.